2017
DOI: 10.1007/s11581-017-2194-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and optical properties of ZnO thin films grown on Si and ITO glass substrates

Abstract: In this study, ZnO thin films have been electrodeposited from zinc nitrate solution without using any catalyst, additive or seed layer on two kinds of substrates (Si and ITO glass).Using cyclic voltammetry and chronoamperometry, it was shown that the mechanism of ZnO deposition strongly depends on the substrate used and its overpotential for nitrate reduction. On Si, the nitrate reduction into nitrite occurs before that of Zn 2+. This reaction induces an increase of the local pH leading to ZnO precipitation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…the XRD characterization of electrodeposited ZnO and Cu 2 O layers on the transparent conductive oxide as the substrate shows the (100), (002), (101), (102) and (110) peaks for ZnO layer and (110), (111), (220) and (222) for Cu 2 O layer (Figs. S3 a,b), which are in accordance with the other reports, confirm the proper formation of these materials 33 , 34 . Moreover, the FESEM analysis of the ZnO deposition shows the homogenous and good coverage of the ZnO nanoparticulated films on the substrate (Fig.…”
Section: Resultssupporting
confidence: 92%
“…the XRD characterization of electrodeposited ZnO and Cu 2 O layers on the transparent conductive oxide as the substrate shows the (100), (002), (101), (102) and (110) peaks for ZnO layer and (110), (111), (220) and (222) for Cu 2 O layer (Figs. S3 a,b), which are in accordance with the other reports, confirm the proper formation of these materials 33 , 34 . Moreover, the FESEM analysis of the ZnO deposition shows the homogenous and good coverage of the ZnO nanoparticulated films on the substrate (Fig.…”
Section: Resultssupporting
confidence: 92%
“…5(a), the rst peak near 386 nm (3.2 eV) may be related to bound excitons. [18][19][20] Some researchers suggested that it is attributed to the UV emission of the radiative recombination of excitons near conduction band levels at the exciton level. 21,22 The second peak in the visible range of 413 nm (3.0 eV) is attributed to transitions from the Sn i level to VBM.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 The second peak in the visible range of 413 nm (3.0 eV) is attributed to transitions from the Sn i level to VBM. 20 The third peak at about 437 nm (2.84 eV) can be attributed to the transition from Sn i to V Sn and from the zinc gap (Zn i ) to the zinc vacancy (V Zn ). [23][24][25] The fourth emission peak of the dominant PL spectrum at about 446 nm (2.78 eV) is attributed to oxygen vacancy-related defects, which results in two donor levels below the conduction band minimum of 1.3-1.6 eV and 0.3-0.5 eV.…”
Section: Resultsmentioning
confidence: 99%